Terpene ketones as natural insecticides against Sitophilus zeamais - Herrera, Jimena María (2015)
The eleven terpene ketones, thymoquinone, (R)-carvone, (S)-carvone, pulegone, dihydrocarvone, menthone, verbenone, ocimenone, camphor, α-thujone and piperitenone, were tested as contact and fumigant insecticides against adults of Sitophilus zeamais Motschulsky under laboratory conditions. The results show that thymoquinone was found to be more toxic than the other ketones, with lethal doses values being LC50 16.5 μg/cm2 and LC50 13.8 μL/L air (24 h after treatment). These ketones were also subjected to multiple regression analysis and the results derived from the quantitative structure activity relationship (QSAR) model suggested two topological indicators, the Balaban and Randic indices, were the best descriptors of insecticidal activity of the ketones. However, orbital electronegativity of the carbonyl group was the main parameter that connected the inhibition activity of ketones on acetylcholinesterase (AChE). Thus, the insecticidal activity of terpene ketones was primarily explained by the shape of molecules and the branching of the carbon-atom skeleton, while inhibition of activity of AChE was mainly due to the electronic descriptors.